2010
DOI: 10.1097/dcc.0b013e3181f0c43c
|View full text |Cite
|
Sign up to set email alerts
|

Critical Care Nurses' Perceptions of Obstacles, Supports, and Knowledge Needed in Providing Quality End-of-Life Care

Abstract: In response to critical care nurses' perceptions of increasing stress and conflict in difficult end-of-life (EOL) situations, the researchers conducted a study to identify perceived obstacles, supports, and knowledge needed to provide quality EOL care. The conclusions were as follows: (1) families and patients need clear, direct, and consistent information to make EOL decisions; (2) physician-related issues affect nurses' ability to provide quality EOL care; (3) critical care nurses need more knowledge, skill,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(79 citation statements)
references
References 13 publications
4
74
0
1
Order By: Relevance
“…Furthermore, she asks for additional specialist nurses in acute hospitals, who should be better educated in the care of the dying and the bereaved. In recent studies, nurses still report on insecurity and lack of education in EOL care (Crump et al, 2010;Espinosa et al, 2010) Nursing education differs among countries and so does education in intensive care nursing. Kirchhoff et al (2003) observed in 2003 that text books in intensive care nursing lacked descriptions of EOL care.…”
Section: The Need For Education and Supportmentioning
confidence: 99%
“…Furthermore, she asks for additional specialist nurses in acute hospitals, who should be better educated in the care of the dying and the bereaved. In recent studies, nurses still report on insecurity and lack of education in EOL care (Crump et al, 2010;Espinosa et al, 2010) Nursing education differs among countries and so does education in intensive care nursing. Kirchhoff et al (2003) observed in 2003 that text books in intensive care nursing lacked descriptions of EOL care.…”
Section: The Need For Education and Supportmentioning
confidence: 99%
“…This obstacle also scored as the largest item in 2 other critical care EOL studies. 7,22 However, in 2 ED studies, 4,5 the item regarding answering telephone calls was ranked as the sixth-largest obstacle. For the critical care nurse samples, this item was highly rated because continual phone calls from family and friends took the nurses away from being at the beside providing care.…”
Section: Discussionmentioning
confidence: 99%
“…6 Perceptions of a "good death" include the idea that the patient is comfortable and free of pain, the family is able to perform EOL rituals, others are respectful of the patient's dignity, and families have adequate time to say goodbye. 7 The EOL experience can be enhanced by eliminating distracting activity and noise to create a quiet, calm atmosphere for the patient and family. 6 Creating such an atmosphere is often difficult in a busy emergency department.…”
mentioning
confidence: 99%
“…Acute and critical care nurses need the skills to care both for patients for whom comfort is the primary goal and for patients who will die under their care; however, in a 2005 national survey by Beckstrand and Kirchhoff 12 and a 2010 replication study, 13 critical care nurses reported that one of the greatest barriers to providing end-of-life (EOL) care was lack of knowledge. Nurses typically choose the critical care practice setting because they want to care for physiologically complex patients, not necessarily dying patients.…”
Section: Palliative/eol Education Initiativesmentioning
confidence: 99%
“…11 Participants also reported an improvement in the effectiveness of their work setting in teaching EOL content, which is encouraging, because one of the greatest barriers to providing EOL care in critical care is lack of knowledge. 13 End-of-life content is also now incorporated into new employee orientation at many of these institutions, so it is spreading beyond the critical care areas.…”
Section: Direct Patient/family Carementioning
confidence: 99%